Unsupervised classification similarity measures, classical and metaheuristic approaches, and applications - Bandyopadhyay, Sanghamitra (Springer, 2013)
This book offers a theoretical analysis of symmetry-based clustering techniques. It includes extensive real-world applications in data mining, remote sensing imaging, MR brain imaging, gene expression data analysis, and face detection.